The determinants of turnover intention among employees in retailing industry - Tan, Jia Mi (2019)
The purpose of this study is to investigate the influence of reward satisfaction and job satisfaction towards turnover intention among frontline employees in retailing industry in Alor Setar. The study also aim to determine the difference in turnover intention between male and female employees. The study was conducted in retail business companies in Alor Setar. This study used quantitative method in which questionnaire has been distributed to collect responses from respondents. From the total of 165 questionnaires distributed to the respondents, 119 questionnaires has been returned and collected. Thus, the response rate is for this study is 72.12% and 119 returned questionnaires which are valid and completed were used in the data analysis process. The data collected was processed using Statistical Package for Sosial (SPSS) version 25. Both descriptive and inferential statistics were used to analyze the data. Result of Multiple Regression Analysis showed that reward satisfaction and job satisfaction significantly and negatively influence turnover intention among employees. Reward satisfaction has the largest contribution to the turnover intention among employees in retailing industry with a beta value of -0.486. In the other hand, finding of Independent Sample T-test showed that there are no difference in turnover intention between male and female employees. Both male and female frontline employees in retailing industry are having the same level of turnover intention. This study contributes to the academic knowledge through providing insights and determining the key factors that influences the most on retail frontline employees’ turnover intention. This study also assist the manager to better understand their frontline employees in terms of turnover intention.